Comparte esto 👍👍DESCARGACAPITULO XIV Operaciones con Fracciones Ejercicio 131Simplificar: 1 m–n + m n 2 – m 2 = 1 m–n – m m 2 – n 2 = 1 m–n – m (m–n ) (m+n ) = 1 m–n [1– m m+n ] = 1 m–n [ m +n– m m+n ] = n m 2 – n 2 x 2 x 2 –xy – 2x y–x = x 2 x (x–y ) + 2x x–y = x x–y + 2x x–y = x+2x x–y = 3x x–y 1 2x– x 2 + x x 2 –4 = 1 x(2–x ) – x 4– x 2 = 1 x(2–x ) – x (2–x ) (2+x ) = 2+x– x 2 x(2–x ) (2+x ) = (2–x )(1+x ) x (2–x )(2+x ) = x+1 x(x+2 ) a+b a 2 –ab + a b 2 – a 2 = a+b a(a–b ) – a a 2 – b 2 = a+b a(a–b ) – a (a+b ) (a–b ) = 1 a–b [ a+b a – a a+b ] = 1 a–b [ (a+b ) 2 – a 2 a(a+b ) ] = 1 a–b [ a 2 +2ab+ b 2 – a 2 a(a+b ) ] = 2ab+ b 2 a( a 2 – b 2 ) x–4 x 2 –2x–3 – x 6–2x = x–4 (x–3 ) (x+1 ) + x 2x–6 = x–4 (x–3 ) (x+1 ) + x 2(x–3 ) = 1 x–3 [ x–4 x+1 + x 2 ] = 1 x–3 [ 2(x–4 ) +x(x+1 ) 2(x+1 ) ] = 1 x–3 [ 2x–8+ x 2 +x 2(x+1 ) ] = 1 x–3 [ x 2 +3x–8 2(x+1 ) ] = x 2 +3x–8 2(x+1 ) (x–3 ) 1 x 2 +2x–8 + 1 (2–x ) (x+3 ) = 1 (x+4 ) (x–2 ) – 1 (x–2 ) (x+3 ) = 1 x–2 [ 1 x+4 – 1 x+3 ] = 1 x–2 [ x+3–(x+4 ) (x+4 ) (x+3 ) ] = 1 x–2 [ x +3– x –4 (x+4 ) (x+3 ) ] =– 1 (x–2 ) (x+4 ) (x+3 ) 1 2x+2 + 2 1–x + 7 4x–4 = 1 2(x+1 ) – 2 x–1 + 7 4(x–1 ) = 2(x–1 ) –8(x+1 ) +7(x+1 ) 4(x–1 ) (x+1 ) = 2x–2–8x–8+7x+7 4( x 2 –1 ) = x–3 4( x 2 –1 ) 2a a+3 + 3a a–3 + 2a 9– a 2 = 2a a+3 + 3a a–3 – 2a a 2 –9 =a[ 2 a+3 + 3 a–3 – 2 (a+3 ) (a–3 ) ] =a[ 2(a–3 ) +3(a+3 ) –2 (a+3 ) (a–3 ) ] =a[ 2a–6+3a+9–2 a 2 –9 ] = a(5a+1 ) a 2 –9 x+3y y+x + 3 y 2 x 2 – y 2 – x y–x = x+3y y+x – 3 y 2 y 2 – x 2 – x y–x = x+3y y+x – 3 y 2 (y–x ) (y+x ) – x y–x = (x+3y ) (y–x ) –3 y 2 –x(y+x ) (y–x ) (y+x ) = xy – x 2 + 3 y 2 –3xy– 3 y 2 – xy – x 2 y 2 – x 2 = –2 x 2 –3xy y 2 – x 2 = 2 x 2 +3xy x 2 – y 2 x x 2 +2x–3 + x–3 (1–x ) (x+2 ) + 1 x+2 = x (x+3 ) (x–1 ) – x–3 (x–1 ) (x+2 ) + 1 x+2 = x(x+2 ) –(x+3 ) (x–3 ) +(x+3 ) (x–1 ) (x+3 ) (x–1 ) (x+2 ) = x 2 +2x–( x 2 –9 ) + x 2 +2x–3 (x+3 ) (x–1 ) (x+2 ) = 2 x 2 +4x–3– x 2 +9 (x+3 ) (x–1 ) (x+2 ) = x 2 +4x+6 (x+3 ) (x–1 ) (x+2 ) 3 2a+2 – 1 4a–4 – 4 8–8 a 2 = 3 2(a+1 ) – 1 4(a–1 ) + 4 8 a 2 –8 = 3 2(a+1 ) – 1 4(a–1 ) + 4 8( a 2 –1 ) = 1 2 [ 3 a+1 – 1 2(a–1 ) + 4 4 (a+1 ) (a–1 ) ] = 1 2 [ 6(a–1 ) –(a+1 ) +2 2(a+1 ) (a–1 ) ] = 1 2 [ 6a–6–a–1+2 2(a+1 ) (a–1 ) ] = 1 2 [ 5a–5 2(a+1 ) (a–1 ) ] = 1 2 [ 5 (a–1 ) 2(a+1 )(a–1 ) ] = 5 4(a+1 ) 1 a–3 + a+1 (3–a ) (a–2 ) + 2 (2–a ) (1–a ) = 1 a–3 – a+1 (a–3 ) (a–2 ) + 2 (a–2 ) (a–1 ) = (a–2 ) (a–1 ) –(a+1 ) (a–1 ) +2(a–3 ) (a–3 ) (a–2 ) (a–1 ) = a 2 –3a+2–( a 2 –1 ) +2a–6 (a–3 ) (a–2 ) (a–1 ) = a 2 –3a+2– a 2 +1+2a–6 (a–3 ) (a–2 ) (a–1 ) = –a–3 (a–3 ) (a–2 ) (a–1 ) = a+3 (3–a ) (a–2 ) (a–1 ) 2x x–1 + 2 x 3 +2 x 2 1– x 3 + 1 x 2 +x+1 = 2x x–1 – 2 x 2 (x+1 ) x 3 –1 + 1 x 2 +x+1 = 2x x–1 – 2 x 2 (x+1 ) (x–1 ) ( x 2 +x+1 ) + 1 x 2 +x+1 = 2x( x 2 +x+1 ) –2 x 2 (x+1 ) +x–1 (x–1 ) ( x 2 +x+1 ) = 2x[( x 2 +x+1 ) –x(x+1 ) ] +x–1 (x–1 ) ( x 2 +x+1 ) = 2x[ x 2 + x +1– x 2 – x ] +x–1 (x–1 ) ( x 2 +x+1 ) = 3x–1 x 3 –1 x+2 3x–1 + x+1 3–2x + 4 x 2 +6x+3 6 x 2 –11x+3 = x+2 3x–1 – x+1 2x–3 + 4 x 2 +6x+3 6 x 2 –2x–9x+3 = x+2 3x–1 – x+1 2x–3 + 4 x 2 +6x+3 2x(3x–1 ) –3(3x–1 ) = x+2 3x–1 – x+1 2x–3 + 4 x 2 +6x+3 (2x–3 ) (3x–1 ) = (2x–3 ) (x+2 ) –(x+1 ) (3x–1 ) +4 x 2 +6x+3 (2x–3 ) (3x–1 ) = (2 x 2 –3x+4x–6 ) –(3 x 2 –x+3x–1 ) +4 x 2 +6x+3 (2x–3 ) (3x–1 ) = 2 x 2 – 3x +4x–6–3 x 2 +x– 3x +1+4 x 2 + 6x +3 (2x–3 ) (3x–1 ) = 3 x 2 +5x–2 (2x–3 ) (3x–1 ) = 3 x 2 –x+6x–2 (2x–3 ) (3x–1 ) = x(3x–1 ) +2(3x–1 ) (2x–3 ) (3x–1 ) = (x+2 )(3x–1 ) (2x–3 )(3x–1 ) = x+2 2x–3 Categories: Capítulo XIV